The impact of campus ostracism on organizational citizenship behavior: The roles of perceived insider status and resilience - Lan Li; Chiyin Chen; Shengqiao Wang (Acta Psychologica, 2025)
Researchers have examined the effects of campus ostracism on students' perceptions, attitudes, and behaviors. However, little is known about the relationships between campus ostracism and student organizational citizenship behavior (OCB). Drawing on social identity theory, we aim to develop and test a moderated mediation model regarding perceived insider status (PIS) as a mediator and resilience as a moderator to explain how and when campus ostracism influences student OCB. A three-wave online survey was conducted and 404 valid data were collected. A linear regression analysis was conducted to test the hypotheses. The results showed that campus ostracism is negatively related to student OCB. PIS mediates this relationship. In addition, our findings indicated that when ostracized students have high resilience, such a relationship between ostracism and PIS and the mediation effect was aggravated. Namely, resilience will enlarge the relationships among campus ostracism, PIS, and OCB. These findings advance our understanding of campus ostracism and suggest that school administrators should adopt strategies to create a friendly campus environment to alleviate campus ostracism and inhibit students' negative behaviors.